Strategi Dakwah melalui Komik di Era Digital: Da'wah Strategy through Comics in the Digital Era - Hidayat, Tatang; Huda, Muchammad Syifaaul; Istianah (QULUBANA: Jurnal Manajemen Dakwah, 2024)
The progress of the times makes dakwah activities not as difficult as the time of the Prophet Shallallahu 'Alaihi Wa Sallam. Many ways are done to broadcast Islam, and comics are one of them. The purpose of this study is to analyze the dakwah strategythrough comics in the digital era. This research uses a qualitative approach and literature study method. Based on the results of the study, comics are a form of media that combines images and text in a series of panels to tell stories. Dakwah message is an expression in Islam that refers to efforts to convey religious teachings to others. The dakwah strategy has undergone significant changes to adapt to technological developments and communication trends. Comics as a digital era dakwah media open up new opportunities to reach a wider audience through online platforms such as social media, websites, and digital comic applications. Digital comics allow direct interaction with readers by commenting, liking, or sharing features on online platforms. Thus, the dakwah message conveyed through comics can be more easily accessed by people around the world.